Does Partisanship Shape Investor Beliefs? Evidence from the COVID-19 Pandemic - J. Anthony Cookson; Joseph Engelberg; William Mullins (ZBW – Leibniz Information Centre for Economics, 2020)
We use party-identifying language – like “Liberal Media” and “MAGA”– to identify Republican users on the investor social platform StockTwits. Using a difference-in-difference design, we find that the beliefs of partisan Republicans about equities remain relatively unfazed during the COVID-19 pandemic, while other users become considerably more pessimistic. In cross-sectional tests, we find Republicans become relatively more optimistic about stocks that suffered the most from COVID-19, but more pessimistic about Chinese stocks. Finally, stocks with the greatest partisan disagreement on StockTwits have significantly more trading in the broader market, which explains 20% of the increase in stock turnover during the pandemic.
Keywords: G12; D91; P16; 330; COVID-19; Partisan; Stock market